METODE INTERPOLASI SPLINE KUADRAT UNTUK PROSES SMOOTHING DATABASE - Dwi Achadiani; Yudi Santoso (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2009)
Quadrate Interpolation Spline is one of method that can be use to approximate the set of point of data. The principle of Interpolation Spline to divice the interval into a collection of subintervals and contruct (generally) different polynomial on each subinterval. The polynomial coefficients are determined by solving a linier system.